A trivalent vaccine candidate against hepatitis E virus, norovirus, and astrovirus. Issue 7 (10th February 2016) - Xia, Ming; Wei, Chao; Wang, Leyi; Cao, Dianjun; Meng, Xiang-Jin; Jiang, Xi; Tan, Ming
Abstract: Hepatitis E virus (HEV), norovirus (NoV), and astrovirus (AstV) are enterically-transmitted viral pathogens causing epidemic or endemic hepatitis (HEV) and gastroenteritis (NoV and AstV) respectively in humans, leading to significant morbidity and mortality worldwide. While a recombinant subunit vaccine against HEVs is available in China, there is no commercial vaccine or antiviral against NoV or AstV. We report here our development of a trivalent vaccine against the three viral pathogens through our new polymer vaccine technology. All HEV, NoV, and AstV are non-enveloped RNA viruses covered by a protein capsid, featuring surface protruding (P) proteins that are responsible for virus–host interaction. These dimeric P proteins elicit neutralizing antibody and are good targets for subunit vaccine development. The trivalent subunit vaccine was developed by fusion of the dimeric P domains of the three viruses together that formed tetramers. This trivalent vaccine elicited significantly higher antibody responses in mice against all three P domains than those induced by a mixture of the three free P domains (mixed vaccine). Furthermore, the post-immune antisera of the trivalent vaccine showed significantly higher neutralizing titers against HEV infection in cell culture and higher blocking activity against NoV binding to HBGA ligands than those of the post-immune sera of the mixed vaccine. Thus, the trivalent vaccine is a promising vaccine candidate against HEV, NoV, and AstV.